Gaya Hidup Halal untuk Pemberdayaan Ekonomi Umat - Naif; Eva Dianawati (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2022)
This study aims to examine the halal lifestyle among Indonesian Muslims. currently Indonesia is lagging behind Malaysia in terms of halal tourism and exports of halal products to foreign countries. besides that this research wants to find out how to improve the halal lifestyle in empowering the people's economy.